2021
DOI: 10.1186/s12576-021-00824-y
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of the central versus peripheral effect of intravenous clonidine using baroreflex equilibrium diagrams

Abstract: Clonidine is a first-generation central antihypertensive that reduces sympathetic nerve activity (SNA). Although clonidine also exerts peripheral vasoconstriction, the extent to which this vasoconstriction offsets the centrally mediated arterial pressure (AP)-lowering effect remains unknown. In anesthetized rats (n = 8), we examined SNA and AP responses to stepwise changes in carotid sinus pressure under control conditions and after intravenous low-dose (2 μg/kg) and high-dose clonidine (5 μg/kg). In the baror… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The neural effect of empagliflozin contrasts with that of clonidine, a central antihypertensive, examined in our previous study using the baroreceptor isolation procedure [ 25 ]. In that study, an intravenous administration of clonidine hydrochloride at 5 μg kg −1 (a cumulative dose of 7 μg kg −1 ) immediately suppressed SNA (the response range was narrowed from 93.9 ± 2.4 to 24.0 ± 6.2%, P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The neural effect of empagliflozin contrasts with that of clonidine, a central antihypertensive, examined in our previous study using the baroreceptor isolation procedure [ 25 ]. In that study, an intravenous administration of clonidine hydrochloride at 5 μg kg −1 (a cumulative dose of 7 μg kg −1 ) immediately suppressed SNA (the response range was narrowed from 93.9 ± 2.4 to 24.0 ± 6.2%, P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…The neural effect of empagliflozin contrasts with that of clonidine, a central antihypertensive, examined in our previous study using the baroreceptor isolation procedure [25]. In that study, an intravenous A previous study demonstrated that a two-week treatment with dapagliflozin decreased the norepinephrine content in the kidneys in high-fat fed mice [26].…”
Section: Effects Of Empagliflozin On Baroreflex Function In Gk Ratsmentioning
confidence: 95%
“…We employed an open-loop analysis of the carotid sinus baroreflex [ 20 ] because this method allows us to test the drug effect on SNA over a wide range of carotid sinus pressure (CSP). For instance, the sympathoinhibitory effect of a central antihypertensive, clonidine, is more evident in the low CSP (high SNA) range than in the high CSP (low SNA) range [ 21 ]. Generally speaking, heart failure causes renal hypoperfusion and induces potential tubular damages [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sympathetic outflow is mainly regulated by activation of the presynaptic α2A subtype, which is the predominant α2R subtype in the brain and exerts an inhibitory role in sympathetic activity [ 20 ]. α2R agonist clonidine serves as the first-generation central antihypertensive drug that reduces sympathetic outflow [ 21 ].…”
Section: Introductionmentioning
confidence: 99%